Analysis of Relation Human Development Index and Economic Growth Regency/City in the Province of West Kalimantan: Analysis of Relation Human Development Index and Economic Growth Regency/City in the Province of West Kalimantan - Juan Pernandes Simamora (Badan Pusat Statistik Provinsi Kalimantan Barat, 2022)
Human development index (HDI) and economic expansion are measures of the welfare of a region. Cointegration and causality of HDI and economic growth of districts/cities in West Kalimantan Province was the focus of this research. Panel data is a combination of cross-sectional data for 14 regions or cities and time series data from 2010 to 2021 in this study case. Klassen typology, cointegration test, and causality test are used in this study to determine the relationship between HDI and economic growth, as well as the long-term relationship or balance between each variable. HDI and economic growth patterns are cointegrated or in balance in the long run. According to the Granger causality test, there is a one-way relationship between HDI and economic growth. Thus, economic growth does have a significant impact on HDI.